Analisis Manajemen Lembaga Tahfidz dalam Meningkatkan Kualitas Bacaan Al-Qur’an Mahasisiwi IIQ Jakarta - Widyastri, Sri; Iskandar, Isman (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2020)
This paper reveals and collaborates descriptively on the management of the Qur'anic tahfidzh institute at the Jakarta Institute of Sciences (IIQ). One of the formal institutions in the field of religious education is rife in the community. Although there have been many formal institutions in the field of religion, especially the Qur'an, which have been successful with a large number of students and good administration, there are also many institutions that have been deflated, especially in urban areas. However, the institution of tahfizh at IIQ Jakarta is increasingly in demand because it shows the achievements of the tahfizh of the Qur'an at national and international levels. This data collection is carried out through document studies, interviews and observations with analytical techniques: 1) Data Reduction, 2) Data Display, 3) Comparative Analysis, and 4) Drawing Conclusions. To maintain the objectivity of the data, a number of appropriate data validity testing techniques are carried out including the credibility test,testing transfer, dataand data triangulation. The results of this study indicate that in the planning of tahsin Al-Qur'an in LTQQ has been well structured because LTQQ formulated it by giving matriculation at the beginning of the semester, fostering tahsin outside of lecture hours and tahsin exams before completing final studies. In each class, students are divided into groups, consisting of 7-10 people and guided by instructors who are appointed by the leadership of IIQ on the proposal of LTQQ and then endorsed by the Chancellor. Evaluating the learning of tahsin Al-Qur'an is done once a week and every time a memorization is made. Evaluation is also carried out at the end of the semester with assessment criteria including: craft, reading fluency, truth of makhraj and tajwid and murattal cleanness. Then this evaluation was reported by each instructor to the LTQQ. Students who have exceeded the specified maqra ' limit, have true makhraj and tajwidnya, and are good at heart, are allowed to take the tahsin exam and are given grades.